Development of social interaction of adolescent onlies biographical sketches - Mapa, Chrisitne Grace E.; Vasquez, Camille Faye L.; Agustin, Estrella R. (2009.)
This study involves the development of the social interaction of adolescent onlies during elementary, high school, and college, highlighting their experiences with parents, relatives, household help, neighbors, and friends. Thirty onlies, aged 17 to 19 years are the respondents for this study. This study utilizes a personal interview in data gathering. Specifically, biographical sketches are written to give a clear picture of the respondents' social experiences. Frequencies and percentages are applied as statistical techniques to analyze data. The results show that the social experiences of the adolescent onlies changed from elementary, high school, and college. As they grow up, their social environment expands from their immediate family, to their relatives to their friends, and to joining school organizations. During elementary, they are with their parents most of the time. They talk about toys, eat together, and go to church. Since parents tend to restrict them socially, the cousins who live nearby serve as channel to their social experiences like playing toys and games. In high school, their parents and cousins still remain as important people to the onlies. They now belong "to barkadas" (cliques) in school. They talk about personal relationships, and go to malls, bars, and clubs. In college, social interaction with their parents, cousins, and friends is sustained. Their social network becomes wider as they join organizations and share academic experiences with school mates. Given the findings of this study, it is highly recommended that Family Life Education seminars must include activities for the onlies of their parents and cousins to strengthen family relationships. Aside from this, one onlies must also join youth camps, organizations, volunteer works, and attend leadership seminars in order to develop socially accepted interaction.
Thesis (BSFLCD)--University of the Philippines Diliman.
Keywords: Social interaction in adolescence; Only child